How tRNAs dictate nuclear codon reassignments: Only a few can capture non-cognate codons - Kollmar, Martin (RNA Biol, 2017)
mRNA decoding by tRNAs and tRNA charging by aminoacyl-tRNA synthetases are biochemically separated processes that nevertheless in general involve the same nucleotides. The combination of charging and decoding determines the genetic code. Codon reassignment happens when a differently charged tRNA replaces a former cognate tRNA. The recent discovery of the polyphyly of the yeast CUG sense codon reassignment challenged previous mechanistic considerations and led to the proposal of the so-called tRNA loss driven codon reassignment hypothesis. Accordingly, codon capture is caused by loss of a tRNA or by mutations in the translation termination factor, subsequent reduction of the codon frequency through reduced translation fidelity and final appearance of a new cognate tRNA. Critical for codon capture are sequence and structure of the new tRNA, which must be compatible with recognition regions of aminoacyl-tRNA synthetases. The proposed hypothesis applies to all reported nuclear and organellar codon reassignments.